Contributions des Plans de Mobilité Urbaine Soutenable en France et au Brésil pour les objectifs d’inclusion sociale - Laura Machado; Livia Salomão Piccinini; Elisabete Arsenio; Odile Heddebaut (Confins)
Sustainable Urban Mobility Plans (SUMP) were presented by the European Commission in 2013 as new tools for planning urban mobility and that should include as main sustainability goals: accessibility and quality of life, as well as sustainability, economic viability, social equity, health and environment quality. This article presents how social inclusion goals are taken into account in planning sustainable urban mobility through sharing experiences in Europe, France and Brazil. The methodology develops an overview of the implementation of SUMP in Europe and presents the case of France, the Member State with higher experience in plan development through the case of the European Metropolis of Lille (MEL). The Brazilian experience is analyzed using a sample of twelve Urban Mobility Plans (PMU) approved by the municipalities. This qualitative analysis illustrates how social equity is considered or not on the planning of urban mobility of cities.